Experimental study on impact fracture characteristics and energy dissipation law of coal under water confining pressure - WANG Kai; FENG Guorui; BAI Jinwen; ZHANG Junliang (矿业科学学报, 2025)
To investigate the actual dynamic fracture process and energy dissipation mechanisms of coal under triaxial loading conditions, a visual experimental study was conducted using a self-developed multi-field coupled Split Hopkinson Pressure Bar (SHPB) testing system. This research systematically examined crack evolution characteristics in coal samples under varying water confining pressure conditions. The relationships between dynamic mechanical parameters (impact velocity, strain rate, and water confining pressure) were quantitatively analyzed, along with the influence of water confining pressure on energy absorption, conversion, and release processes during coal failure. The research results show that the dynamic strength of coal shows obvious strain rate effect under water confining pressure environment. There is a good quadratic function relationship between water confining pressure and the dynamic strength of coal mass, and the failure strain of coal samples shows a decreasing trend with the increase of water confining pressure. With the increase of water confining pressure, the fracture mode of coal mass will change from "axial splitting failure" to "compression-shear failure". The greater the impact load, the higher the total energy input to the coal body and the dissipated energy used for damage and deformation, and the more serious the deformation of the coal body. With the increase of water confining pressure, the total input energy shows a trend of gradual increase, and more energy is required from the outside when the coal body is damaged.